Harry Potter and the Chamber of Secrets - Rowling, J. K. (Arthur A. Levine Books, 1999)
When the Chamber of Secrets is opened again at the Hogwarts School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.